2021
DOI: 10.1007/s10989-021-10255-3
|View full text |Cite
|
Sign up to set email alerts
|

Quest for Novel Preventive and Therapeutic Options Against Multidrug-Resistant Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa ( P. aeruginosa ) is a critical healthcare challenge due to its ability to cause persistent infections and the acquisition of antibiotic resistance mechanisms. Lack of preventive vaccines and rampant drug resistance phenomenon has rendered patients vulnerable. As new antimicrobials are in the preclinical stages of development, mining for the unexploited drug targets is also crucial. In the present study, we designed a B- and T-cell multi-epitope vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Vaccine efficacy may be enhanced by building chimeric vaccines. Bioinformatic analysis further confirmed that these kinds of vaccines are effective and highly stable [ 67 , 68 , 69 ].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
See 3 more Smart Citations
“…Vaccine efficacy may be enhanced by building chimeric vaccines. Bioinformatic analysis further confirmed that these kinds of vaccines are effective and highly stable [ 67 , 68 , 69 ].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…PA is classified as multi-drug resistant (MDR), characterized by a number of virulence factors and an adaptable genome, which will make the microorganism able to overlap the ongoing treatments. For this reason, the research for new antibiotics and antivirulence compounds is pursued simultaneously with that for vaccines against P. aeruginosa [ 65 , 66 , 67 ]. Vaccine targets include factors that trigger the immune response in the host, characterized by antigenic elements typically found on the bacterial surface, such as lipopolysaccharides (LPS) and outer membrane proteins (OMPs) [ 68 ].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
See 2 more Smart Citations